2020
DOI: 10.1016/j.cgh.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of COVID-19-Related Liver Functional Abnormality

Abstract: BACKGROUND & AIMS:Some patients with SARS-CoV-2 infection have abnormal liver function. We aimed to clarify the features of COVID-19-related liver damage to provide references for clinical treatment. METHODS:We performed a retrospective, single-center study of 148 consecutive patients with confirmed COVID-19 (73 female, 75 male; mean age, 50 years) at the Shanghai Public Health Clinical Center from January 20 through January 31, 2020. Patient outcomes were followed until February 19, 2020. Patients were analyz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
644
7
23

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 733 publications
(768 citation statements)
references
References 21 publications
45
644
7
23
Order By: Relevance
“…(which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. those of previous studies, which have shown associations between older age, male sex, unmediated inflammatory response to infection, and lymphopenia with increased risks of AICU admission for severe complications (18,20,21).…”
Section: Discussionmentioning
confidence: 48%
“…(which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. those of previous studies, which have shown associations between older age, male sex, unmediated inflammatory response to infection, and lymphopenia with increased risks of AICU admission for severe complications (18,20,21).…”
Section: Discussionmentioning
confidence: 48%
“…33,36 Liver injury may occur after the use of multiple drugs, such as antivirals, antibiotics, traditional Chinese medicine, antipyretics and analgesics. 7,10 Although liver histology is poorly accessible in COVID-19, few studies have already reported pathological findings on autopsies performed on SARS-CoV-2 infected patients. Xu et al observed microvesicular steatosis and mild lobular and portal activity.…”
Section: Covid -19 and Hepati C Inj Urymentioning
confidence: 99%
“…All rights reserved Coronavirus disease 2019 (COVID-19) leads to elevated liver biochemistries in 15% to 53% of patients. (1)(2)(3)(4)(5)(6)(7) The profile of admission biochemistries is most frequently an aspartate aminotransferase (AST) or alanine aminotransferase (ALT) elevation, with alkaline phosphatase or total bilirubin elevations more rarely reported. (8) Severe cases of COVID-19 have higher liver biochemistries on admission.…”
mentioning
confidence: 99%